2012
DOI: 10.1117/12.924298
|View full text |Cite
|
Sign up to set email alerts
|

Self-induced laser line sweeping and self-pulsing in double-clad fiber lasers in Fabry-Perot and unidirectional ring cavities

Abstract: 8 pagesInternational audienceRare-earth doped fiber lasers are subject to instabilities and various self-pulsed regimes that can lead to catastrophic damage of their components. An interesting self-pulsing regime accompanied with laser wavelength drift with time is the so called self-induced laser line sweeping (SLLS). Despite the early observations of the SLLS in solid-state ruby lasers, in fiber lasers it was first time mentioned in literature only in 2009 where such a laser wavelength drift with time was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…Indeed, the SLLS may trigger the self-Q-switched regime of fiber lasers. In the case of a self-swept ring fiber laser, the self-Q-switched regime was observed from a certain pump power level, while for the same setup with carefully suppressed parasitic reflections and no SLLS the self-Q-switched regime was not observed [7,13,15,16]. Lobach et al also confirmed that, in the time domain, the SLLS regime has the character of single or few simultaneously oscillating modes and discovered that frequency increment during the sweeping procedure equates to frequency intermodal spacing [14,17].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Indeed, the SLLS may trigger the self-Q-switched regime of fiber lasers. In the case of a self-swept ring fiber laser, the self-Q-switched regime was observed from a certain pump power level, while for the same setup with carefully suppressed parasitic reflections and no SLLS the self-Q-switched regime was not observed [7,13,15,16]. Lobach et al also confirmed that, in the time domain, the SLLS regime has the character of single or few simultaneously oscillating modes and discovered that frequency increment during the sweeping procedure equates to frequency intermodal spacing [14,17].…”
Section: Introductionmentioning
confidence: 97%
“…An interesting type of instability is the selfinduced or spontaneous laser line sweeping (SLLS) regime. Despite early observation of the SLLS in ruby lasers [3], this type of instability was observed in fiber lasers only recently, both in Fabry-Perot [4,5] and ring cavity arrangements [6,7] based on ytterbium active medium emitting near 1.08 μm. Peculiar to this regime is spontaneous but steady sweeping of the laser line within a certain spectral range, with a line jump between the final and starting positions of the sweep range.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was also demonstrated that in some conditions one can obtain sweeping in the so-called reverse direction. The reverse self-sweeping was reported for the first time in [6]. The instantaneous spectrum can contain many longitudinal modes or have only one mode (single-frequency self-sweeping operation) depending on the cavity parameters [5].…”
Section: Introductionmentioning
confidence: 99%
“…Эффект самосканирования обусловлен тем, что во время генерации в активной среде возникают динамические решетки коэффициента усиления и показателя преломления, которые влияют на генерацию последующих мод, что приводит к постоянному изменению спектра выходного сигнала [4]. В волоконных лазерах наблюдается ска-нирование длины волны генерации как в сторону увеличения [4], так и в сторону уменьшения [5]. Наиболее популярным направлением явля-ется изучение сканирования в иттербиевых волоконных лазерах вблизи 1 мкм [2][3][4], однако не прекращаются попытки расширения диапазона сканирования за счет использования других активных сред.…”
unclassified